In this tutorial, I go through using f(x) or g(t) notation. You will be shown what we mean by writing notation like f(x+1), 3f(x),-f(x) or g(t), 5g(-1) and given the opportunity to do several examples.

You will be asked to combine functions. In this tutorial, you are shown what we mean by combining functions and introduced to a simple example and the notation that you may expect to see.

Examples in the video

If f(x) = 2x – 3, g(x) = 3 / x where x ≠ 0 and h(x) = x^{2}

Find:

- fg(x)
- gfh(x)
- fff(x)

### Example

## Example 1

Examples in the video

If f(x) = e^{2x + 1}, g(x) = 2x – 4 and h(x) = ln x

Find:

- fg(x)
- hf(x)
- fh(x)

### Example 1

## Example 2

Examples in the video

If f(x) = e^{2x + 1}, g(x) = 2x – 4 and h(x) = ln x

Find:

- fg(x)
- hf(x)
- fh(x)

### Example 2

If you are not sure what an inverse function is or how to find one then this video should hopefully show you.

## Example 3

Examples in the video

If f(x) = (3x – 2) / 8, find f^{– 1}(x)

- If f(x) = (3x – 2) / 8, find f
^{– 1}(x)

### Example 3

Inverse Example on Handling more than 1 ‘x’ term.

In this example the aim is to have two x values in the function and show that you can use other letters other than f(x)

## Example

Examples in the video

- If g(x) = (2x – 3) / (x – 1), x ε ℝ, x ≠ 1, Find g-1(x)